Multikriterielle Entscheidungsunterstützung für die Synthese von Herstellprozessen zur Fertigung funktional gradierter Bauteile - Rudtsch, Vinzent; Gausemeier, Jürgen; Petersen, Marcus
Functional gradation denotes a continuous distribution of properties over at least one spatial dimension of a component made of single material. This distribution is tailored with respect to the later intended application of the component. The improved material utilization enables light weight design and reduced resource consumption, thus offering an alternative for modern composite materials. To support the production planner in setting up the required manufacturing processes, this contribution proposes a multi-criteria decision-support approach that is based upon a framework for the computer-aided planning and optimisation of functionally graded components. The obtained ranking of possible process chains then allows the production planner to select the best alternative.

Mechanisms interdisciplinary {\ "a} r cooperation in product discovery - approaches ä approaches for collaborative generation of ideas - Eckelt, Daniel; Placzek, Markus

Specification Technique for the Consistent Description of Manufacturing Operations and Resources - Rehage, Gerald; Bauer, Frank; Gausemeier, Jürgen

Multi-Criteria Decision-Support for Manufacturing Process Chain Selection in the Context of Functionally Graded Components - Petersen, Marcus; Rudtsch, Vinzent; Gausemeier, Jürgen
In this contribution a methodology for a multi-criteria decision-support for manufacturing process chain selection in the context of functionally graded components is presented. The basis for this decision-support is provided by a framework for the computer-aided planning and optimisation of manufacturing process chains of functionally graded components, which is still under development. To distinguish between several alternative process chains it is necessary to consider those decision criteria that can not explicitly be specified within the CAD model. A matrix-supported algorithm guarantees a consistent weighting of these decision criteria while enabling a fine-granular rating scale. As a result, a ranking of the different process chains is achieved that constitutes the basis for the decision maker to select the favourite alternative.

A Concept of Camera Test-Bench for Testing Camera Based Advanced Driver Assistance Syytems - Tan, Yin; Hassan, Bassem (Proceedings of the ASME 2011 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (CIE))

Virtual Test Environment for Self-Optimizing Systems - Stöcklein, Jörg; Müller, Wolfgang; Baldin, Daniel; Xie, Tao

Successful action against product piracy - Peter, Stefan; Eckelt, Daniel; Kliewe, Daniel (Mechanical engineering and metalworking Germany)

A Method for Testing Camera Based Advanced Driving Assistance Systems - Tan, Yin; Hassan, Bassem (Proceedings of ISAM (IEEE International Symposium on Assembly and Task Planning))

Reconfigurable Driving Simulator for Testing and Training of Advanced Driver Assistance Systems - Hassan, Bassem; Berssenbrügge, Jan; Al Qaisi, Imad; Stöcklein, Jörg (Proceedings of ISAM (IEEE International Symposium on Assembly and Task Planning)

A Framework for the Computer-Aided Planning and Optimization of Manufacturing Process Chains in the Context of Functionally Graded Components - Petersen, Marcus; Gausemeier, Jürgen
Functional gradation denotes a continuous distribution of properties over the spatial dimensions of a component. These distributions are tailored with respect to later applications and require complex manufacturing processes. Therefore, a framework for the planning and optimization of manufacturing process chains for those components is presented. The framework is divided into three modules – the Component Description for the integration of graded properties into CAD models, the Expert System for the synthetization of alternative process chains and the Model-based Process Chain Optimization.

Automatic Verification of Modeling Rules in Systems Engineering for Mechatronic Systems - Kaiser, Lydia; Dumitrescu, Roman; Holtmann, Jörg; Meyer, Matthias (Proceedings of the ASME International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)
Mechatronics is the close interaction of mechanics, electronics, control engineering and software engineering. The increasing complexity of mechatronic systems results in a challenging development process and particularly requires a consistent comprehension of the tasks between all the engineers involved. Especially during the early design phases, the communication and cooperation between the mechanical, electrical, control and software engineers is necessary to establish a basis for efficient and effective product development. The approach of Model-Based Systems Engineering focuses on this aspect by means of an abstract but superordinate system model. It enables a holistic view of the system. The system model can be specified using the Systems Modeling Language (SysML). The language allows many degrees of freedom to specify a fact, bearing in mind that different system architects can specify the same fact in different ways. This leads to system models that can be interpreted in many ways. Thus, these models are hard to consistently compare and interpret, resulting in communication issues. In order to tackle this problem, we present a concept that uses modeling rules supporting model comparability. We formalize them by means of checks implemented in the programming language Java and the Object Constraint Language (OCL) in order to automatically verify the system model’s compliance with these rules.

GPU-Based Local Tone Mapping in the Context of Virtual Night Driving - Berssenbrügge, Jan; Bonner, Erik

Future-oriented Research Strategies for Additive Manufacturing - Gausemeier, Jürgen; Peter, Stefan; Wall, Marina (Proceedings of Rapid.Tech 2013)

Cross-Industry Innovations – Systematic Identification and Adaption - Echterhoff, Niklas; Amshoff, Benjamin; Gausemeier, Jürgen (Proceedings of the International Conference on Innovation and Management and Technology (ICIMT))

GPU-basiertes lokales Tone-Mapping für Nachtfahrsimulatoren - Bonner, Erik; Berssenbrügge, Jan

Systematic Identification of Cross-Industry Innovations using Bibliometrics - Echterhoff, Niklas; Amshoff, Benjamin; Gausemeier, Jürgen (Proceedings of the 22nd International Conference on Management of Technology)

Kaskadierte Simulationen und Visualisierungen für die Analyse mechatronischer Systeme in umfangreichen Transportszenarien - Hassan, Bassem; Klaas, Alexander; Wassmann, Helene; Grafe, Michael

Procedural Model for the Virtual Commissioining on the Basis of Model-based Design - Schmuedderich, Tanja; Trächtler, Ansgar; Brökelmann, Jan; Gausemeier, Jürgen

Systems Engineering Management Based on a Discipline-Spanning System Model - Gausemeier, Jürgen; Gaukstern, Tobias; Tschirner, Christian

Approach for an Early Validation of Mechatronic Systems using Idealized Simulation Models within the Conceptual Design - Bauer, Frank; Gausemeier, Jürgen; Köchling, Daniel; Oestersötebier, Felix